3D Bioprinting: Biologically Inspired Smart Release System Based on 3D Bioprinted Perfused Scaffold for Vascularized Tissue Regeneration (Adv. Sci. 8/2016). Issue 8 (August 2016) - Cui, Haitao; Zhu, Wei; Holmes, Benjamin; Zhang, Lijie Grace
Abstract : In the article 1600058, Lijie Grace Zhang and co‐workers develop a comprehensive design of engineered vascularized bone construct (top image), integrating biomimetic 3D printed fluid perfused microstructure with a biologically inspired smart growth factor release system (colored fibers). The design provides great potential for complex tissue/organ regeneration by delivering multiple growth factors (small spheres), in a highly coordinated manner based on appropriate time, location and biological signal.